The Reservation Wage Curve: Evidence from the UK - Sarah Brown; Karl Taylor (Institute for the Study of Labor (IZA), 2014)
We investigate the relationship between an individuals' reservation wage, i.e. the lowest wage acceptable in order to enter into employment, and unemployment in the local area district. Largely unexplored in the literature this adds to the work which has examined the association between employee wages and unemployment the 'wage curve'.
Keywords: J64; J31; R23; 330; wage curve; reservation wages; unemployment